Information and Knowledge Management in Complex Systems 16th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2015, Toulouse, France, March 19-20, 2015. Proceedings - Liu, Kecheng; Nakata, Keiichi; Li, Weizi; Galarreta, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 16th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2015, held in Toulouse, France, in March 2015. The 21 revised papers presented were carefully reviewed and selected from 46 submissions. The papers are organized in the following topical sections: organisational semiotics: theory and concepts; organisational semiotics and applications; information systems and services; complex system modeling and simulation; and innovation and organisational learning.
A Generative Grammar for Modal Syntagms -- A Semiotic Approach to Critical Reasoning -- Information Systems and Sign Systems -- On the Relationships between Norms, Values and Culture: Preliminary Thoughts in HCI -- A Semiotic Approach to Investigate Quality Issues of Open Big Data Ecosystems -- Virtual Process Control Modelling in Organisational Semiotics: A Case of Higher Education Admission -- Assessing Pragmatic Interoperability for Process Alignment in Collaborative Working Environment -- Clarifying the Situational Context of a TV Company towards the Design of iDTV Applications -- Applying Organizational Semiotics for Developing Knowledge-Based Cost Estimation of Construction Project -- Designing Natural User Interfaces Scenarios for All and for Some: An Analysis Informed by Organizational Semiotics Artifacts -- An Evolution Method of Service View Products Supported Dynamic Integration of Information Resources -- The Adoption of Smartphones Among Older Adults in China -- Towards Automatic Generation of Project-Based Solutions -- Translation of Requirements Engineering Models -- An Optimization of Collaborative Filtering Personalized Recommendation Algorithm Based on Time Context Information -- A Meta-heuristic Approach for Copper Price Forecasting -- Complexity Management in the Semiconductor Supply Chain and Manufacturing Using PROS Analysis -- Simulation on Resident Individual Trip Choice Decision Making: Based on Modeling of Rough Set and Genetic Algorithms -- Visualization of the UK Stock Market Based on Complex Networks for Company$1 (Bs Revenue Forecast -- Creativity Filter and Start-Ups to Resolve the Innovation Paradox -- The Relationship between Flexible Human Resource Management and Enterprise Innovation Performance: A Study from Organizational Learning Capability Perspective.s
Keywords: Computer science; Information technology; Business -- Data processing; Application software; Computer Science; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; IT in Business; Electronic books